Intrahousehold influence on contraceptive use among married Indian women: Evidence from the National Family Health Survey 2015–16 - Ranjan, Mukesh (SSM Popul Health, 2020)
BACKGROUND: India, where more than one married woman of reproductive age often live in the same household, provides an ideal setting to promote family planning through intrahousehold influence. OBJECTIVES: This study examined the association between use of modern contraceptives by young married women, and other married women live in the same household. METHODS: We included 31,361 currently married women of 15–24 years from women data of the National Family Health Survey 2015–16. Each of these women was living with another married woman within the same household, who was also interviewed. From each household, we labeled the woman with the shortest marital duration as the Index Woman. The second woman in each household was either labeled as Peer or Other or Elderly (had married within 5 years or 5–19 years after or 20 or more years after the marriage of Index women, respectively). The association between use of modern contraceptives by Index Women and the second woman in household was examined using logistic regressions—controlled for the background characteristics of Index Women. RESULTS: Index Women had 2.9 times adjusted odds (95%CI 2.5–3.3) of using modern contraceptives if living with Peers, who were also using modern contraceptives. Similarly, when the second women using modern contraceptives, an Index Woman had 1.7 times adjusted odds for using modern contraceptives (95%CI 1.5–1.9) if living with Elderly, and about 2.5 times adjusted odds if living with Other women (95%CI 2.1–2.8). The association between contraceptive use by an Index Woman and the second woman in the household remained significant even after controlling for background characteristics, showing the independent effect of intrahousehold influence on contraceptive use. CONCLUSION: The conclusive evidence of positive intrahousehold influence on contraceptive use of Index Women will encourage program managers to promote intrahousehold communication to increase use of family planning.